A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam - Lam, Truong Xuan (Zootaxa, 2019)
Emesopsis konchurangensis sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae: Ploiariolini) is described from central Vietnam as the fourth species of the genus in this country. A key to the Vietnamese species of Emesopsis is presented.